Recent advances in functional assays of WRKY transcription factors in plant immunity against pathogens - Wang, Wenjing; Cao, Haihui; Wang, Jiahao; Zhang, Hongbo (Frontiers in Plant Science, 2025)
WRKY transcription factors (TFs) are one of the largest transcription factor families in plants and play important roles in plant processes, most notably in responding to diverse biotic and abiotic stresses. This article reviews the recent research progresses on WRKY TFs in regulating plant immunity, which includes both positive and negative regulation. WRKY TFs were shown to regulate plant defense against pathogens including fungi, bacteria, oomycetes, and viruses by modulating downstream pathogen resistance genes or interacting with other regulators. Plant signaling pathways or components involved in the regulatory network of WRKY-mediated plant immunity mainly involve the action of phytohormones, MAPKs (Mitogen-activated protein kinases), and other transcription factors. The interaction of WRKY TFs with these factors during pathogen resistance was discussed in this article, which may contribute to understanding the mechanisms of WRKY transcription factors in plant immunity.